The characteristics of ginsenosides and oligosaccharides in mountain‐ and garden‐cultivated ginseng. (15th September 2020) - Zhu, Lianlian; Luan, Xiaoning; Yuan, Ying; Dou, Deqiang; Huang, Luqi
Abstract: BACKGROUND: The present study aimed to explore the chemical characteristics of mountainous forest cultivated ginseng (MFCG) and garden ginseng (GG) with respect to their ginsenosides and oligosaccharides. METHODS: A high‐performance liquid chromatography with diode‐array detection‐evaporative light‐scattering detection technique was adopted to investigate the ginseosides and oligosaccharides of GG and MFCG. RESULTS: The features of ginsenosides showed Rg1/Re in different parts of GG and MFCG: main root > lateral root > fibrous root, as well as Rg1/Re in the main root: MFCG > GG, indicating that the Rg1/Re is related to age of the ginseng. In most cases, Rg1/Re < 1 in entire GG and Rg1/Re > 1 in entire MFCG. In addition, the ratio of protopanaxadiol/protopanaxatriol in main root of GG is approximately 1 and, in the main roots of MFCG, the ratio is approximately 2 and, furthermore, Ro/Rb1 of MFCG is lower than that of GG. Analysis of oligosaccharides showed that GG mainly contained sucrose and MFCG mainly contained sucrose and maltose, and the ratio of sucrose to maltose was at least more than 4:1 in GG and less than 4:1 in MFCG in most cases, indicating the characteristics of oligosaccharides of MFCG are primarily affected by its growing environment. The results also showed that ginsenoside Re is most probably the biosynthetic precursor of ginsenoside Rg1 (i.e. Re was synthesized first and then transformed to Rg1 in vivo ). CONCLUSION: The characteristics of Rg1/Re and higher maltose can be regarded as one of the characteristics of high quality MFCG, and these characteristics are related to a higher age and the cultivation environment of ginseng. The formation mechanism of these characteristics for GG and MFGG is also discussed. As far as we know, the present study is the first to determine the difference of Rg1/Re and oligosaccharides between MFCG and GG and this provides a reference for the quality control criterion of GG and MFCG. © 2020 Society of Chemical Industry